Managing Pre-Construction and Construction Risks on Project Sites in Abuja-Nigeria - Richard A. Jimoh; Momoh A Sani; Abdulahi I Adoza; Isah Yahaya (Institute of Research and Community Outreach - Petra Christian University, 2016)
Managing risks in construction projects has been acknowledged as a key direction process for the purposes of attaining the project goal in terms of time, cost, quality, safety, and environmental sustainability. Hence, the paper evaluated pre-construction and construction risks on active project sites in Abuja-Nigeria. This was achieved using survey method through the self-administration of 35 questionnaires to the professionals handling the 35 identified projects being undertaking at that time. Results showed that errors and omissions in design and improperly defined project scope had mean score values of 3.03 and 2.54, respectively, were the construction risks most experienced by the professionals during pre-construction. On the other hand, fluctuation in market prices and delays with mean score values of 3.14 and 2.74, respectively, were the construction risks experienced by the professionals during the construction phase of the projects. It is recommended that procurement methods such as construction management should be adopted and stakeholders should keep to their own side of the bargain to avoid unnecessary delays.